Knowledge Gaps between Farmers and Scientists: A Case Study on Perceptions and Knowledge on Arabica Coffee Pests and Diseases of Mount Elgon, Uganda - Liebig, Theresa Ines; Jassogne, Laurence T.P.; Rahn, Eric; Läderach, Peter R.D.; Poehling, Hans-Michael; Kucel, Patrick; Asten, Piet J.A. van; Avelino, Jacques (2015)
In this paper, we present a case study on coffee production in Uganda, a sector depending mostly on smallholder farming facing a simultaneous and increasing number of socio-ecological pressures. The objectives of this study were (i) to examine and relate FPK on Arabica Coffee Pests and Diseases (CPaD) to altitude and the vegetation structure of the production systems, (ii) to contrast results with perceptions from experts and (iii) to validate results with field observations, in order to identify constraints for improving information flow from scientists to farmers and back.The presented study was conducted in the framework of the BMZ-funded project entitled Trade-offs and synergies in climate change adaptation and mitigation in coffee and cocoa systems . The GOAL of the project is the adaptation of vulnerable coffee/cocoa-based farming systems to climate change that combine improving farmer income and system resilience with contributing to climate change adaptation and mitigation. The PURPOSE is the adoption of new production technologies in cocoa/coffee-based smallholder farming systems that (i) are adapted to climate change, (ii) contribute to climate change mitigation, (iii) sustain the natural resource base, and (iv) respond to livelihoods needs and constraints.